OPTIMASI KEUNTUNGAN PENJUALAN MENGGUNAKAN METODE SIMPLEX BERBASIS QM FOR WINDOWS (Studi kasus: UMKM Es Teh Jumbo Mas Jawa) - Beti costantina Bonay; Heru Sutejo, Lusiana Watung, Nonike Bahabol, Josua Petrus Ajokwapi, Rani Pangky, Sisten Keroman, Kos (CV. Adiba Aisha Amira, 2026)
This study aims to formulate an optimal daily sales mix for Es Teh Jumbo using linear programming, the simplex method, and QM for Windows. The research problem is the need to determine the production quantity of three main beverages under limited time, raw materials, and market demand. The variables are X1 for original iced tea, X2 for sweet orange drink, and X3 for Milo plus Good Day. Data were obtained from field observation and interview, then completed with realistic operational assumptions for coefficients that were not yet available in the first field report. The objective function maximizes daily profit with contribution margins of IDR 4,000, IDR 5,000, and IDR 6,500 per cup. The constraints include production time, tea water, sugar water, ice, orange raw material, total daily sales, and product demand limits. The QM for Windows result shows an optimal solution of 140 cups of X1, 60 cups of X2, and X3 of 100 cups with a maximum profit of Rp1,510,000 per day. This finding shows that the Maximum simplex method can help beverage UMKM in making more measurable, efficient, and profit-maximizing production decisions.